PENGEMBANGAN MODEL PELATIHAN MEDIASI SEBAYA UNTUK MENGURANGI PERILAKU AGRESI RELASI SISWA (Tarbiyah, 2014)
A Peer Mediation Training Model Development for Reducing Studentsâ Relational Aggression Behavior. The school environment is not always comfortable for apart of the students, one of the causes is conflict among students which is manifested in relational aggression behavior. The peer mediation training model need to be made for diminishing the relational aggression behaviors that appeared among the students at that schools. However, in fact, there is not any training model that can be used to provide the mediator students at the junior high schools. For assisting school counselors, the school providestraining through which the peer mediation training model needs to be made. The product evaluations were requested to two expert evaluators, seven counselors after the training simulation done, and forty eight training participants from two SMPs.The evaluation results of experts, counselor in the small group try-out, studentsâ evaluation and counselor in limited field try-out and revision which had been carried out indicated that training material and strategycould be stated that it was appropriate to be used.